Macroscopic signs of deterioration of medicines in home stocks (Research, Society and Development, 2021)
There are few studies in the literature that assess the quality of medicines stored in patients homes. Thus, this study aimed to describe the presence of macroscopic signs of deterioration in pharmaceutical forms found in home stocks medicines. This is a descriptive observational study that used data from an interview conducted between August 2014 and July 2016 in the homes of 423 users assisted in primary health care (PHC) in a medium-sized city in Minas Gerais. The assessment of deterioration was performed by two previously trained researchers who followed parameters established in the literature. The description of the results was made using absolute and relative frequency. 21 (5%) of the 423 households visited had at least one medicine with a macroscopic sign of deterioration. A frequency of 7.5% (n=24) of deteriorated medicines was found, with this deterioration being present both in medicines that were within 3.2% (n=7) and out of date 4.8% (n=4). Of the other 13 medicines that were deteriorated, it was not possible to verify the expiration date. The study evidenced a low frequency of macroscopic deterioration in the medicines found in the patients home stock. It is noteworthy that the deterioration did not only occur in expired medicines, a fact that can be explained by the poor storage conditions at home.